Python Parallel Programming Cookbook - Zaccone, Giancarlo (Packt Publishing, 2015)
Unleash the full potential of Python for parallel programming with 'Python Parallel Programming Cookbook.' This book teaches you how to write code that performs multiple tasks simultaneously, enhancing efficiency and computational power. You'll explore topics such as threading, multiprocessing, asynchronous programming, and GPU utilization, all through practical Python examples.What this Book will help me doUnderstand and apply threading and process-based parallelism in Python programming.Implement message-passing communication to manage parallel tasks across processes.Master GPU programming using PyCUDA to tackle computationally intensive problems.Leverage Python frameworks and libraries for distributed parallel computing applications.Adopt asynchronous event-driven programming models to design efficient applications.Author(s)None Zaccone is an experienced Python programmer and educator who specializes in parallel and distributed computing techniques. With a background in teaching and development, None has guided many learners through complex programming concepts, providing clear and insightful explanations. His approach emphasizes practicality and clarity, making technical topics accessible and actionable for developers.Who is it for?This book is ideal for Python developers who are looking to explore or deepen their knowledge of parallel programming techniques. It's perfect for those with an intermediate to advanced skill level in Python and seeks to optimize performance in their applications. If you're a developer interested in distributed systems, GPU programming, or asynchronous programming, this book will give you the fundamental and advanced tools needed to succeed.